PEMBERDAYAAN LEMBAGA PENDIDIKAN FORMAL DI BANGKA DALAM PENANAMAN GEREJA BARU - Daniel Abdi; Yanto Paulus Hermanto (Sesawi, 2021)
Social concern in the formation of Christian character and faith through non-profit educational institutions that have not been a special concern of Christians. Meanwhile, Christ must be the main part in the character of church leadership and secular leadership in the future. Through formal educational institutions such as Kindergartens and Elementary Schools, the church can contribute in participating in the intellectual life of the nation from an early age with the principle of 'fearing God'. Educational institutions are long-term in the formation of the character of Christ which plays an important role for each generation in the welfare and salvation of generations. The Sustainability Service can be expanded to carry out joint activities. the evidence of the new church is as true church growth. Several strategies developed through the empowerment of formal educational institutions, and under the leadership of the Holy Spirit, are expected to contribute to the planting of new churches.Keywords: Social Care, Formal educational institutions, Fear of God